Multicellular membranes as an in vitro model for extravascular diffusion in tumours. - Cowan, D. S. (Nature Publishing Group, 1996)
Efficient extravascular diffusion is a critical requirement for hypoxic cell radiosensitisers, bioreductive drugs and hypoxic cell markers that must reach cells distant from functional blood vessels in tumours. The diffusion of simple nitroimidazoles with neutral (misonidazole, miso) and basic (pimonidazole, pimo) side chains, as well as 2-nitroimidazoles with acridine (NLA-1) and phenanthridine (2-NLP-3) DNA intercalating moieties was investigated using multicellular membranes (MMs), a new in vitro model for the extravascular compartment of tumours. The diffusion of miso through V79 MMs was concentration independent over the range 0.1-10 mM. Mathematical modelling of the flux kinetics provided a diffusion coefficient in MMs (DMM) of 5.5 x 10(-7) cm2 s-1 which was approximately 13-fold lower than in culture medium. Flux was little affected by the extent of hypoxia in MMs, indicating that hypoxic metabolism does not compromise diffusion of miso over distances in the order of 200 microns. The DMM for pimo was similar to miso, while those for 2-NLP-3 and NLA-1 were both lower. The results demonstrate compromised extravascular diffusion for DNA-intercalating nitroimidazoles, but indicate that this problem is more severe for the basic acridine derivative, NLA-1, than for the phenanthridine, 2-NLP-3. The MM model appears to be well suited to quantitative determination of drug diffusion in a multicellular environment.